The The Analysis of Small and Medium Enterprises and Tax Capital in Economic Regional Growth - Adetia Azmi Tanjung; Endrianur Rahman Zain (Institute of Computer Science (IOCS), 2020)
The objective of this research is to examine the significance of increasing capital in Small and Medium Enterprises development regional economy in the Asahan Regency. The method stages to be used in this research are the research flow chart, data collection, literature study, problem identification, preprocessing, data analysis used is multiple linear regression, normality test, classical assumption test, statistical tests or the coefficient of determination (R2), statistical F test, and statistical t-test), results of data analysis, final evaluation, research approach, location and time of research, and tools and materials. The independent effect on the dependent variable. From the results of statistical calculations that have been done, it can be seen that the F count> F table. Namely F count is 6.20 while the F table is 3.191. Thus, H0 is rejected and the variables of capital and tax have an effect simultaneously and positive for the regional economy.